Enhanced Polypropylene Production with Amoco CD Catalyst: Organotitanium Complex on MgCl\(_2\) - Arzoumanidis, Gregory G. (Scientific Research, New Technologies and Applications Vol. 2, 2024)
A MgCl2-supported catalyst with controlled particle size was developed specifically for the Amoco-Chisso gas phase process. Complete control of the final catalyst morphology and particle size is achieved by optimizing parameters such as precipitation temperature, THF/Mg mole ratio, aging conditions, chemical composition, stirring rate, and the choice of Mg compounds and electron donors. The resulting Amoco CD catalyst, based on anhydrous magnesium chloride and titanium compounds activated with triethylaluminium, exhibits excellent particle size distribution, high bulk density, good fluidity, and high activity. Both lab and pilot scale preparation methods are detailed, and polymerization tests in bench and pilot scale reactors demonstrate the catalyst’s effectiveness. The median particle size (d50) of the catalyst can be controlled within the range of 7-100 microns. Parameters influencing PS and PSD during catalyst support preparation include agitation speed, temperature, organic reagent to Mg ratios, morphology-controlling agents, and the deliberate spiking of the aromatic solvent with appropriate contaminants. Variations in particle shape, ranging from cubic to spheroidal, are affected by the reagents used, the ratios of reagents to Mg, the time/temperature profile of the procedure, and the sequence of reagent addition during catalyst support preparation. Catalyst activation occurs in several steps through thermal treatment of the support with TiCl4/toluene solutions. A cost-effective TiCl4/toluene reuse system from the activation streams has been implemented to significantly reduce waste material. The optimum activation temperature is approximately 120°C. Progress of activation and catalyst quality can be monitored by IR spectroscopy, with identifiable IR fingerprint patterns correlating well with catalyst performance. A new concept of organotitanium complexes as catalysts coordinated on MgCl2 support, operating independently, but in tandem with the traditional TiCl4 polymerization active centers has been introduced. The new catalysts with dual activity centers based on CD technology demonstrate improved performance and advantageous polymer product properties. We propose that the dual-activity concept applied to several organometallic complexes may herald a new era in MgCl2-supported polyolefin catalysis, including single-site catalysts activated by TEA and the production of advanced polyethylene copolymers. The success of the CD and Amoco-Chisso gas-phase process is illustrated by the two dozen commercial plants worldwide using the technology and the licensing advances by INEOS, the successor of Amoco, for this polypropylene technology.